Liquidity Constraints and Deforestation: The Limitations of Payments for Ecosystem Services - Jayachandran, Seema (American Economic Review, 2013)
A popular environmental policy is to pay forest owners for avoiding deforestation on their land. This is an example of “payments for ecosystem services” (PES). This paper shows that liquidity constraints can limit the effectiveness of PES programs. If an individual would have cut down trees to sell them, his opportunity costs are more front-loaded than the stream of PES income. If credit constrained, he might decline the program even if the net present value (NPV) of the PES income exceeds the NPV of his opportunity costs. I present evidence consistent with this prediction using data on forest owners in Uganda.